Implementasi Public Relations Pariwisata - Akbar Maulana Isman; Ani Yuningsih (Bandung Conference Series: Public Relations, 2024)
Abstract. Public Relations of Belitung Regency Tourism Office as public relations to build tourism image of Belitung Regency, needs to take an action to build tourism image by promotion through maras taun event. Maras taun is a traditional activity carried out every year with the aim of expressing gratitude for the rice harvest obtained. From these activities can be a tourist attraction for tourists. This research uses a case study method with data collection techniques of observation, in-depth interviews and documentation. From the results of this study, it is known that the strategic steps of Public Relations are distributing letters to the Village organizers of the maras taun event to find out when and where the maras taun is held, then published in the calender of events of the Belitung Regency Tourism Office. Then managing messages through video content with local wisdom value by searching for data through various existing sources, then published to the official Instagram of the Belitung Regency Tourism Office. The reason for using Instagram as a social media platform for the Belitung Regency Tourism Office is the ease of reaching audiences, the ease of accessing Instagram and other supporting features. Abstrak. Public Rerlations Dinas Pariwisata Kabupaten Belitung sebagai humas untuk membangun citra pariwisata Kabupaten Belitung, perlu melakukan sebuah aksi untuk membangun citra pariwisata dengan cara promosi melalui event maras taun. Maras taun merupakan kegiatan adat yang dilaksanakan setiap tahun dengan tujuan untuk mengungkapkan rasa syukur atas panen padi yang didapat. Dari kegiatan tersebut bisa menjadi daya tarik wisata bagi wisatawan. Penelitian ini menggunakan metode studi kasus dengan teknik pengumpulan data observasi, wawancara mendalam dan dokumentasi. Dari hasil penelitian ini, diketahui langkah-langkah strategis Public Relations yaitu menyebarkan surat kepada Desa penyelenggara acara maras taun untuk mengetahui kapan dan dimana pelaksanaan maras taun tersebut, kemudian dimuat dalam calender of event Dinas Pariwisata Kabupaten Belitung. Kemudian pengelolaan pesan melalui konten video bernilai kearifan lokal dengan mencari data melalui berbagai sumber yang ada, kemudian dipublikasikan ke Instagram resmi Dinas Pariwisata Kabupaten Belitung. Alasan penggunaan Instagram sebagai platform media sosial bagi Dinas Pariwisata Kabupaten belitung adalah kemudahan menjangkau khalayak, kemudahan dalam mengakses Instagram dan fitur penunjang lainnya.